Message in a bottle - Costner, Kevin; Wright, Robin 1966-; Mandoki, Luis; Sparks, Nicholas; De Novi, Denise; Wilson, Jim; DiPego, Gerald (Warner Home Video (Phils.), 1999)
A reporter traces a lonely widower who wrote a heart-felt message, put it in a bottle, and threw it in the sea.